Burmese grape fruit juice can trigger the "logic gate"-like colorimetric sensing behavior of Ag nanoparticles towards toxic metal ions. Issue 30 (3rd March 2015) - Alam, Md Niharul; Chatterjee, Anirban; Das, Sreeparna; Batuta, Shaikh; Mandal, Debabrata; Begum, Naznin Ara
Abstract : Ag NPs synthesized by Burmese grape fruit juice showed selective Hg 2+ sensing activity. Abstract : We report here a very effective, economically viable and environment-friendly protocol for the synthesis of stable, crystalline, spherical Ag nanoparticles (NPs) with appreciable monodispersity using the Burmese grape ( Baccaurea ramiflora Lour.; family: Phyllanthaceae) fruit juice as a green multifunctional agent (GMA) under sonochemical condition. These nanoparticles showed strong and selective Hg 2+ ion-sensing activity (in μM level), analogous to the molecular logic gate function, in aqueous medium over a wide range of pH (3.73–11.18), which is based on their visual color change, and hence the change in their surface plasmon resonance (SPR) peak position and intensity. Phytochemical screenings of the GMA were also done to identify its active constituents responsible for the rapid synthesis, stabilization and selective sensing activity of the Ag NPs. The Ag NP surface-adsorbed functionalities, which are from these active biomolecules, induced a change in aggregation behavior of these NPs, which ultimately enhanced the ion-sensing activity of these NPs compared to citrate-, CTAB-, SDS- and PVP-stabilized Ag NPs synthesized by chemical method. Moreover, the use of this non-toxic, green multifunctional agent may confer biocompatibility to the Ag NPs, opening up the possibility for their use in the in vivo detection of toxic heavy metal ions.